CCNP Switch portable command guide - Empson, Scott (Cisco Press, 2010)
CCNP SWITCH Portable Command Guide All the SWITCH 642-813 Commands in One Compact, Portable Resource Scott Empson Hans Roth Preparing for the CCNP ® exam? Working as a network professional? Here are all the CCNP-level commands for the Implementing Cisco ® Switched Networks (SWITCH) exam you need in one handy resource. The CCNP SWITCH Portable Command Guide is filled with valuable, easy-to-access information and is portable enough for use whether you're in the server room or the equipment closet. This book helps you memorize commands and concepts as you work to pass the CCNP SWITCH exam (642-813). The guide summarizes all CCNP certification-level Cisco IOS ® Software commands, keywords, command arguments, and associated prompts, providing you with tips and examples of how to apply the commands to real-world scenarios. Configuration examples throughout the book provide you with a better understanding of how these commands are used in simple network designs. Use CCNP SWITCH Portable Command Guide as a quick, offline resource for research and solutions. --Logical “how-to” topic groupings inside the front and back covers provide one-stop research --Compact size makes it easy to carry with you, wherever you go --Helps you review important commands before taking the CCNP SWITCH certification exam --“Create Your Own Journal” appendix with blank, lined pages allows you to personalize the book for your own needs This book is part of the Cisco Press ® Certification Self-Study Product Family, which offers readers a self-paced study routine for Cisco certification exams. Titles in the Cisco Press Certification Self-Study Product Family are part of a recommended learning program from Cisco Systems ® that includes simulation and hands-on training from authorized Cisco Learning Partners and self-study products from Cisco Press.